"Clinical Dentistry Effects of Covid 19" - Холбоева Н.А; Музаффаров А.Ш; Шафоатова Г.А; Носирова Г.Б (Zien Journals, 2022)
The aim of this study was to determine the rate of cracks and other etiologic factors during the period of March 16th to May 31st in 2020 (COVID-19 initial outbreak) and 2021 (COVID-19 ongoing pandemic) compared with figures from the same period in 2019 (pre-COVID era) in 2 endodontists’ practices.
Keywords: Cracked teeth; endodontists’ practices